Influence of dispositional factors on quality service delivery in two university libraries in Oyo State, Nigeria (2021)
One of the objectives of university libraries is to become relevant in information service delivery and to provide quality service to their users. Previous studiesrevealed that some users are not satisfied with the service rendered in university libraries. This study therefore examined influence of dispositional factors (perception, attitude and satisfaction) on quality service (tangibility, reliability, responsiveness, assurance, empathy) delivery in two university libraries in Oyo State, Nigeria.The study was anchored to Expectancy Disconfirmation Theory, while the survey research design of correlational type was adopted. Two universities in Oyo State were selected for the study; University of Ibadan (UI) and AjayiCrowther University (ACU). Two stage and total enumeration sampling techniques were adopted to select participants from the two university libraries under study respectively. A total of 431 participants which comprised postgraduate students and library personnel were selected. The instruments used were dispositional factors scale (r=0.98), contextual factors scale (r=0.76) and servqual scale (r=0.97). Data were analysed using descriptive statistics, pearson’s product moment correlation and multiple regression at 0.05 level of significance.There was high students’ perception of quality service in the two universities (𝑥̅=29.8), library personnel attitude towards students was positive (𝑥̅=27), students’ level of satisfaction of library services was high (𝑥̅=29.98).The state of quality service delivered was high (𝑥̅=68.60). There were significant relationship between dispositional factors and quality service delivery; students’ perception (r=.632), library personnel attitude (r=.480), students’ satisfaction (r=.620). Dispositional factors influenced quality service delivery among postgraduate students in universities in Oyo State, Nigeria. Library personnel should exhibit positive attitude towards library users, most especially postgraduate students in order to improve their use of the library